2016
DOI: 10.20517/2394-4722.2016.42
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and breast cancer biomarkers: the case of the cytochrome P450 2E1

Abstract: Aim:The aim of the study is to investigate the impact of the cytochrome P450 2E1, which is the most efficient CYP450 family member in generating reactive oxygen species (ROS), on cellular energy metabolism of breast cancer cells and therefore the effects of CYP2E1 on breast carcinogenesis. Methods: The estrogen receptor positive MCF-7 and the triple negative MDA-MB-231 breast cancer cells were used as experimental system to estimate ROS generation in these cells overexpressing CYP2E1 and treated with the glyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 57 publications
(78 reference statements)
1
5
0
Order By: Relevance
“…1 mM H2O2, the MCF7 cells showed a 4-fold increase in SOH signal whereas for the MDA-MB-231 we recorded a 1.5-fold increase, relative to their starting basal levels. These data support previous findings showing variable basal levels of SOHs in different cells [38][39][40], which may be related to differences in the redox state of each specific cell line [41][42][43]. Noteworthy, we observed a distinct response between the two cell lines to the oxidative stress caused by treatment with H2O2, with the MCF7 being 2.6 times more susceptible than MDA-MB-231 in increasing the amount of SOHs following the addition of H2O2.…”
Section: Cellular Localization and Levels Of Protein Sulfenylation Insupporting
confidence: 90%
“…1 mM H2O2, the MCF7 cells showed a 4-fold increase in SOH signal whereas for the MDA-MB-231 we recorded a 1.5-fold increase, relative to their starting basal levels. These data support previous findings showing variable basal levels of SOHs in different cells [38][39][40], which may be related to differences in the redox state of each specific cell line [41][42][43]. Noteworthy, we observed a distinct response between the two cell lines to the oxidative stress caused by treatment with H2O2, with the MCF7 being 2.6 times more susceptible than MDA-MB-231 in increasing the amount of SOHs following the addition of H2O2.…”
Section: Cellular Localization and Levels Of Protein Sulfenylation Insupporting
confidence: 90%
“…In addition, antioxidant biomarker FRAP was associated with higher diet quality index score at baseline. Previous studies had investigated FRAP in women with breast cancer [ 42 , 43 , 44 ]. Evidence has shown that FRAP values were proportional to the reducing power of the main nonenzymatic antioxidants in plasma [ 27 ]; thus, this assay was selected to assess the antioxidant status of women with breast cancer in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Sateesh et al [ 42 ] found values of FRAP in women with breast cancer lower than the ones recorded for healthy women; this finding indicates that the disease leads to decreased nonenzymatic antioxidant defenses. Singh et al [ 44 ] found lower FRAP values after neoadjuvant chemotherapy application in women with breast cancer, which evidenced an even greater reduction in nonenzymatic antioxidant defense caused by the treatment. According to the present investigation, it seems that patients’ diet can enhance the nonenzymatic antioxidant defenses reduced by the disease, and it likely has a protective effect against oxidative damage in the case of lack of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Hormonal factors are relevant in the development of breast tumors. These factors are strongly related to oxidative stress (OS) through the generation of reactive oxygen species (ROS) as Subir Singh, Ramkumar Rajendran, et al [38] demonstrated in their study. They did a comparative study on two groups, namely one group with positive hormonal breast cancer receptors and another with negative hormonal receptors.…”
Section: Figure 5 Fras For the Studied Group Accordingmentioning
confidence: 99%